Symbol-error rate analysis of Fischer's bit-loading algorithm - Seyedi, A.; Saulnier, G.J. (IEEE transactions on communications, 2004)
We obtain an analytical result for the symbol-error rate of a wireless orthogonal frequency-division multiplexing system employing Fischer's bit-loading algorithm. First we assume that the subchannel coefficients are statistically independent, then we extend the results to the case with dependent subchannel coefficients. Throughout the analysis, we assume that the number of subchannels is large, and that subchannels have Rayleigh-distributed coefficients. The comparison of analytical and simulated results shows that the approximation error is small, especially at low noise and high bit rate.